(untitled) (Nexo Revista Científica, 2021)
According to the regulatory and environmental requirements on operating waterworks facilities referred to as objects of activity, the environmental influence of these facilities must be assessed in terms of water resource utilization, which is exactly the goal of this study. The basics of the methodology of this assessment are developed by the system approach centred around the notion of System. The results of studying the interaction of the object of activity (OA) with the natural environments (NENV) of the basin geosystem are used in developing the basics of the methodology of environmental influence assessment (EIA). The study results have been used in designing and building hydropower engineering facilities in the North Caucasus in the South of Russia.